Transformasi Pengelolaan Perpustakaan Sekolah dalam Perspektif Manajemen Pendidikan Modern - Septia Angraini; Muhammad Munawir Pohan (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2026)
School libraries can be used strategically to improve students' literacy culture. The purpose of this study is to describe the transformation that occurs in school library management from the perspective of modern educational management. This study uses a descriptive qualitative method. Data were collected through direct observation and in-depth interviews with librarians, principals, teachers, and students. The results of the study indicate that the library of SMPN 1 Sungai Penuh has experienced significant development in its function and role. The library has evolved from simply a place to store books to a more active learning space that supports students' literacy activities. This transformation is demonstrated by the increased comfort of the reading room, the development of collections relevant to the curriculum, the involvement of librarians in literacy activities, and collaboration between teachers and librarians in the learning process. Sustainable library development depends on the support of the principal and positive responses from students. This is done even though technology is still limited and library management is not yet fully digital. It found that the reading culture and quality of learning in schools are gradually improved through participatory library management.